ED50 of remimazolam combined with different doses butorphanol for first trimester artificial abortion - Chen, Jinming; Li, Xiaoling; Hu, Zilan; Zheng, Yuling; Mai, Ying; Zhang, Zhongqi (Frontiers in Medicine, 2024)
Introduction Remimazolam (RMZ) is a novel intravenous sedative drug of ultra-short benzodiazepine. The optimal dose of RMZ plus butorphanol for sedation during first trimester artificial abortion is unknown. Therefore, the present study aimed to evaluate the median effective dose (ED50) of RMZ combined with different doses of butorphanol on the sedative effect for first-trimester artificial abortion. Methods Sixty-one female patients were randomly assigned to Group B10 (31 patients) and Group B15 (30 patients). RMZ was administered 5 min after IV butorphanol at doses of 10 μg/kg (Group B10) and 15 μg/kg (Group B15). Cervical dilatation at the time of using a cervical dilating rod, if the patient has body movement and affects the gynecologist’s operation, we define it as “Ineffective.” Therefore, the dose of RMZ was increased in the next patient. Otherwise, it was defined as “Effective,” and the dose of RMZ was reduced in the next patient. According to the pre-experiment, the first dose of RMZ in the first patient was 0.35 mg/kg, and the adjacent geometric dose ratio was 0.9. The centered isotonic regression was performed to determine the ED50 of RMZ. The total RMZ dose administered, recovery time, and anesthesia-related adverse events were all recorded. Results The ED50 (90% CI) of RMZ was 0.263 (0.215–0.310) mg/kg in Group B10, and 0.224 (0.191–0.261) mg/kg in Group B15, respectively. The recovery time in Group B10 was significantly shorter than in Group B15 (9.8 ± 2.3 vs. 12.5 ± 3.6 min, p ≤ 0.001). There was no significant difference in the incidence rate of all anesthesia-related adverse events between the two groups (p > 0.05). Conclusion The ED50 of RMZ combined with a 10 μg/kg or 15 μg/kg dose of butorphanol was 0.263 and 0.224 mg/kg during painless first trimester artificial abortion. However, RMZ combined with a 10 μg/kg dose of butorphanol seems to have a shorter recovery time. Clinical trial registration https://www.chictr.org.cn/bin/project/edit?pid=166623.